Pembentukan Republik Demokratik Rakyat Laos: Peralihan dari Monarki ke Negara Sosialis pada Tahun 1975 - Rizkiardi, Tamam (Lani: Jurnal Kajian Ilmu Sejarah dan Budaya, 2025)
This research discusses the establishment of the Lao People's Democratic Republic (Lao PDR) in 1975, marking the country's transition from a constitutional monarchy to a socialist state. The study aims to analyze the key factors that played a role in this power shift, including the role of the communist Pathet Lao movement, the involvement of foreign nations such as North Vietnam and the United States, as well as the impact of this transition on Laos' socio-political conditions. Through a literature review and historical analysis, the research shows that Pathet Lao's victory was supported by favorable geopolitical conditions and significant backing from North Vietnam. The main findings indicate that this change not only ended the monarchy but also had a profound effect on the social, political, and economic stability of Laos.